PENERAPAN PAJAK PENGHASILAN (PPh) PASAL 21 TERHADAP PEGAWAI TETAP PT. GRAHA SENTOSA PERMAI CABANG PALANGKA RAYA - Ellydia Ludang (JOURNAL SOCIO ECONOMICS AGRICULTURAL, 2019)
Income Tax Article 21 is a type of tax that applies in full to employees both Government Employees and Private Employees who will make a significant contribution to state revenue. The application needs to be carried out in an order and continuous manner in accordance with the law used to regulate the amount of tax rates, the procedures for payment and the tax reporting, namely Act No. 36 of 2008. The purpose of this study is to determine the application of Income Tax Article 21 Permanent Employees at PT. Graha Sentosa Permai Palangka Raya branch, whether it is in accordance with applicable regulations. The method used in this research is descriptive method. The calculation of Income Tax Article 21 conducted by PT. Graha Sentosa Permai Palangka Raya Branch has not yet fully complied with the regulations resulting in a lack of deposit of the Income Tax Article 21. This is due to the differences in the calculation of the cost of the office where the company does not make calculations in accordance with applicable law and the underpayment will be paid by the company before the income tax return is submitted. PT. Graha Sentosa Permai, Palangka Raya branch, besides providing salaries, also provides food allowances and overtime pay for employees and provides a Holiday Allowance once a year, which is just before Eid Mubarrak that all permanent employees can get.